Prefronto-striatal physiology is associated with schizotypy and is modulated by a functional variant of DRD2 - Taurisano, Paolo; Romano, Raffaella; Mancini, Marina; Giorgio, Annabella Di; Antonucci, Linda A.; Fazio, Leonardo; Rampino, Antonio; Quarto, Tiziana; Gelao, Barbara; Porcelli, Annamaria; Papazacharias, Apostolos; Ursini, Gianluca; et al. (Frontiers in Behavioral Neuroscience, 2014)
“Schizotypy” is a latent organization of personality related to the genetic risk for schizophrenia. Some evidence suggests that schizophrenia and schizotypy share some biological features, including a link to dopaminergic D2 receptor signaling. A polymorphism in the D2 gene (DRD2 rs1076560, G>T) has been associated with the D2 short/long isoform expression ratio, as well as with striatal dopamine signaling and prefrontal cortical activity during different cognitive operations, which are measures that are altered in patients with schizophrenia. Here, our Our aim is to determine the association of schizotypy scores with the DRD2 rs1076560 genotype in healthy individuals, as well as and their interaction on with prefrontal activity during attention and D2 striatal signaling. A total of 83 healthy subjects were genotyped for DRD2 rs1076560 and completed the Schizotypal Personality Questionnaire (SPQ). Twenty-six 26 participants underwent SPECT with [123I]IBZM D2 receptor radiotracer, while 68 performed an attentional control task during fMRI. We found that rs1076560 GT subjects had greater SPQ scores than GG individuals. Moreover, the interaction between schizotypy and the GT genotype predicted prefrontal activity and related attentional behavior, as well as striatal binding of IBZM. No interaction was found in GG individuals.These individuals. These results suggest that rs1076560 GT healthy individuals are prone to higher levels higher levels of schizotypy, and that the interaction between rs1076560 and schizotypy scores modulates phenotypes related to the pathophysiology of schizophrenia, like such as prefrontal activity and striatal dopamine signaling. These results provide systems-level qualitative evidence for mapping the construct of schizotypy in healthy individuals onto the schizophrenia continuum.